Interaction domain in non-prestressed circular concrete bridge piers using simplified modified compression field theory - Abouelleil, Alaaeldin (Kansas State University, 2015)
The importance of the analysis of circular columns to accurately predict their ultimate confined capacity under shear-flexure-axial force interaction domain is recognized in light of the extreme load event imposed by the current AASHTO LRFD specification. In this study, various procedures for computing the shear strength are reviewed. Then, the current procedure adopted by AASHTO LRFD 2014, based on the simplified modified compression field theory, is evaluated for non-presetressed circular concrete bridge piers. This evaluation is benchmarked against experimental data available in the literature and against Response 2000 freeware program that depicts interaction diagrams based on AASHTO 1999 requirements. Differences in results are discussed and future improvements are proposed. A new approach is presented to improve the accuracy of AASHTO LRFD calculations. The main parameters that control the cross section shear strength are discussed based on the experimental results and comparisons.
Keywords: Shear Analysis; Simplified Modified Compression Field Theory; Moment-Shear interaction diagrams; Civil Engineering (0543)